1996
DOI: 10.3354/meps142225
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of debris on the deep sea floor off the French Mediterranean coast

Abstract: The distribution and abundance of large marine debris were investigated on the continental slope and bathyal plain of the northwestern Mediterranean Sea during 3 oceanographic cruises undertaken in June 1994, July 1995 and April 1996. Different types of debris were enumerated, particularly pieces of plastic, plastic and glass bottles, metallic objects, glass and diverse materials including flshing gear. The results showed considerable geographical variation, with concentrations ranging from 0 to 78 pieces of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
147
2
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 210 publications
(163 citation statements)
references
References 8 publications
9
147
2
5
Order By: Relevance
“…The geographic distribution of debris on the ocean floor is strongly influenced by hydrodynamics, geomorphology and human factors (Galgani et al 1996;Pham et al 2014). Moreover, there are notable temporal variations, particularly seasonal, with tendencies for accumulation and concentration of marine litter in particular geographic areas (Galgani et al 1995).…”
Section: Seafloormentioning
confidence: 99%
See 4 more Smart Citations
“…The geographic distribution of debris on the ocean floor is strongly influenced by hydrodynamics, geomorphology and human factors (Galgani et al 1996;Pham et al 2014). Moreover, there are notable temporal variations, particularly seasonal, with tendencies for accumulation and concentration of marine litter in particular geographic areas (Galgani et al 1995).…”
Section: Seafloormentioning
confidence: 99%
“…Only few studies have assessed debris below 500 m depth (June 1990;Galil et al 1995;Galgani et al 1996Galgani et al , 2000Galgani and Lecornu 2004;Keller et al 2010;Miyake et al 2011;Mordecai et al 2011;Bergmann and Klages 2012;Wei et al 2012;Pham et al 2013Pham et al , 2014Ramirez-Llodra et al 2013, Schlining et al 2013Fischer et al 2015;Vieira et al 2014);Galgani et al (2000) observed trends in deep-sea pollution over time off the European coast with an extremely variable distribution and debris accumulating in submarine canyons. Miyake et al (2011) recorded debris down to 7,216 m depth in video surveys from the Ryukyu Trench.…”
Section: Seafloormentioning
confidence: 99%
See 3 more Smart Citations